1991
DOI: 10.1148/radiology.178.1.1824582
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacomechanical thrombolysis and angioplasty in the management of clotted hemodialysis grafts: early and late clinical results.

Abstract: The results of pharmacomechanical thrombolysis and angioplasty of 121 thrombosed hemodialysis grafts were reviewed. The initial pharmacomechanical method (used in 65 cases) employed clot maceration with hook-shaped catheters and clot lacing with highly concentrated urokinase. The current technique (used in 56 cases) consisted of pulsed-spray injection of urokinase into the clot. All fully treated grafts (117 cases) underwent complete or near-complete thrombolysis, and 93% remained patent after 1 day. Mean time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
5

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(81 citation statements)
references
References 0 publications
2
74
0
5
Order By: Relevance
“…[8 -19] These methods include pulse-spray thrombolysis with urokinase supplementation and balloon maceration of residual clot, [8,9] crossed catheter pharmacomechanical thrombolysis, [10] and mechanical thrombectomy using thrombectomy catheter and clot aspiration. [14,15] These methods have reported technical success rates of 75% 92%, but experiences were limited to PTFE grafts.…”
Section: Discussionmentioning
confidence: 99%
“…[8 -19] These methods include pulse-spray thrombolysis with urokinase supplementation and balloon maceration of residual clot, [8,9] crossed catheter pharmacomechanical thrombolysis, [10] and mechanical thrombectomy using thrombectomy catheter and clot aspiration. [14,15] These methods have reported technical success rates of 75% 92%, but experiences were limited to PTFE grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Access patency is limited by the development of fistula stenosis either at the venous anastomotic site or in the downstream vein. These stenoses cause more than 80% of AV access thromboses [5,6], which themselves account for 80-85% of AV access failures.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term results for dialysis grafts demonstrate primary and secondary patency rates at 1 year of 26% and 51%, respectively. 34 These results compare with 60-70% patency rates reported for surgical revision at 1 year. 35 With patients maintained on hemodialysis for longer periods of time, thrombolytic therapy can help preserve access sites.…”
Section: Venous Thrombolysismentioning
confidence: 65%
“…32 Several studies have demonstrated the efficacy of thrombolytic therapy in preserving long-term patency and viability of the access grafts. [32][33][34] In addition, thrombolytic therapy has allowed for improved evaluation of underlying venous limb stenosis predisposing to stasis and thrombosis. Long-term results for dialysis grafts demonstrate primary and secondary patency rates at 1 year of 26% and 51%, respectively.…”
Section: Venous Thrombolysismentioning
confidence: 99%